Integrating Board Games in Primary Classrooms to Build Dynamic Learning Environments: A Systematic Review - Yuliani, Aulia; Juhana, Agus (STKIP PGRI Bandar Lampung, 2025)
In recent years, the development of educational technology has provided various tools to create more interactive and engaging learning methods. One increasingly popular approach is gamification, which has proven effective in enhancing student engagement and motivation. Learning media such as board games hold significant potential to strengthen active student participation, provide enjoyable learning experiences, and foster the development of their social and cognitive skills. Based on this premise, this study aims to analyze the effectiveness of board games as an educational tool to enhance the engagement of elementary school students. The authors employed a Systematic Literature Review to examine research on the effectiveness of board games as an educational medium for improving student engagement in elementary schools. Data mining was conducted using Publish or Perish with relevant keywords such as